Glucose Sensor O-GlcNAcylation Coordinates with Phosphorylation to Regulate Circadian Clock. - Kaasik, K.; Kivimäe, S.; Allen, J.J.; Chalkley, R.J.; Huang, Y.; Baer, K.; Kissel, H.; Burlingame, A.L.; Shokat, K.M.; Ptá?ek, L.J.; Fu, Y.H. (Cell Metabolism, 2013)
Posttranslational modifications play central roles in myriad biological pathways including circadian regulation. We employed a circadian proteomic approach to demonstrate that circadian timing of phosphorylation is a critical factor in regulating complex GSK3?-dependent pathways and identified O-GlcNAc transferase (OGT) as a substrate of GSK3?. Interestingly, OGT activity is regulated by GSK3?; hence, OGT and GSK3? exhibit reciprocal regulation. Modulating O-GlcNAcylation levels alter circadian period length in both mice and Drosophila; conversely, protein O-GlcNAcylation is circadianly regulated. Central clock proteins, Clock and Period, are reversibly modified by O-GlcNAcylation to regulate their transcriptional activities. In addition, O-GlcNAcylation of a region in PER2 known to regulate human sleep phase (S662-S674) competes with phosphorylation of this region, and this interplay is at least partly mediated by glucose levels. Together, these results indicate that O-GlcNAcylation serves as a metabolic sensor for clock regulation and works coordinately with phosphorylation to fine-tune circadian clock.